Equal access of COVID‐19 vaccine distribution in Africa: Challenges and way forward - Aborode, Abdullahi T. (J Med Virol, 2021)
The World Health Organization (WHO) in Africa and Africa Center Disease Control (Africa CDC) urge the international community and different countries in Africa to ensure sustainable and concrete action to ensure equal and easy access to the COVID‐19 vaccines, as different countries in Africa are still struggling to develop a safe and effective strategy to ensure equal vaccine distribution, if available. Africa CDC has called on the international community to come together to help Africa with COVID‐19 vaccines to make equal the vaccine distribution among African countries as many cannot afford the vaccine costs due to the level of poverty and other negative factors. The African Union has endorsed the need for Africa to develop a framework to actively engage in easy accessibility to COVID‐19 vaccines, which will allow different countries in Africa to take easy steps that will strengthen the local vaccine distribution system, building workforce skills and knowledge, and enrich outreach services in Africa. The article discusses the need for equal access in the distribution of COVID‐19 vaccines in Africa, the challenges, and the necessary recommendations that can help to mitigate these challenges.